Integrin but not CEACAM receptors are dispensable for Helicobacter pylori CagA translocation - Zhao, Qing; Busch, Benjamin; Jiménez-Soto, Luisa Fernanda; Ishikawa-Ankerhold, Hellen; Massberg, Steffen; Terradot, Laurent; Fischer, Wolfgang; Haas, Rainer (PLOS Pathogens, 2018)
Author summary The Cag Type IV secretion system of Helicobacter pylori (Hp) interacts with host cell integrins and injects the bacterial oncoprotein CagA into host cells thereby contributing to inflammation and carcinogenesis during chronic infection. Binding of β1 integrin receptors by the CagA protein and the type IV secretion system is well described by many research groups, but its function for CagA translocation is not well understood. We report here that this interaction is not essential for the function of the secretion system and for CagA injection into the gastric epithelial cells lines AGS and KatoIII. However, the bacterial binding to a set of specific receptors called carcinoembryonic antigen-related cell adhesion molecules (CEACAMs) by the Hp outer membrane protein HopQ is a prerequisite for CagA translocation. Interestingly, other bacterial adhesins and the mediated binding events do not have a similar effect on CagA translocation, suggesting a specific feature associated with HopQ mediated binding.